Inductive powering of subcutaneous stimulators: key parameters and their impact on the design methodology - Carmen Godfraind; Adrien Debelle; Laurent Lonys; Vicente Acuña; Pascal Doguet; Antoine Nonclercq (PAGEPress Publications, 2016)
Inductive powering of implantable medical devices involves numerous factors acting on the system efficiency and safety in adversarial ways. This paper lightens up their role and identifies a procedure enabling the system design. The latter enables the problem to be decoupled into four principal steps: the frequency choice, the magnetic link optimization, the secondary circuit and then finally the primary circuit designs. The methodology has been tested for the powering system of a device requirering a power of 300mW and implanted at a distance of 15 to 30mm from the outside power source. It allowed the identification of the most critical parameters. A satisfying efficiency of 34% was reached at 21mm and tend to validate the proposed design procedure.